Did Mozart Suffer from Gilles de la Tourette Syndrome? (2017)
The personal and private lives of great men and women in history, like writers, painters and musicians, have been the subject of great interest for many years. A clear example of this is the vast scrutiny is cast over the famous composer, Wolfgang Amadeus Mozart. What may have started as curiosity, rapidly evolved into extensive research, as the answers about the musician's legendary talent may lie in the details of his life (his childhood, his relationships, his quirks and his mannerisms). It is usually up to historians, anthropologists or philosophers to delve into the pages of old books, trying to grasp answers and clues. However, for some time, Physicians have sought their own part in solving the puzzle. The long told hypothesis regarding Mozart's diagnosis of Gilles de la Tourette syndrome will be examined. Could all of the peculiarities and oddities of the genius be caused by a neurological disorder? Or was this musical genius just an eccentric brilliant man?. © 2016 Asociación Colombiana de Psiquiatría